Impact of integrated nutrient management on ginger production - Singh, AK; Gautam, US; Singh, Jai (Bangladesh Journal of Botany, 2018)
An experiment was evaluated in an integrated approach of nutrient management on two ginger cultivars under irrigation domains in Kymore Plateau and Satpura Hills zone of central India for three consecutive years during the kharif season. The results revealed that the weight of rhizomes per plant and fresh rhizome yield together with VC ratio were noted to be significantly higher (229.9 g and 22754 kg/ha) in improved cultivar Suprabha with integrated nutrient management (INM) in partial shade than the same genotype with INM without shade (216.4 g and 21692 kg/ha). The lowest rhizome per plant and fresh rhizome yield was recorded in farmers’ practice (without shade) with Local cultivar (154.7 g and 16698 kg/ha). The technology gap and technology index were minimum in improved cultivar Suprabha with INM due to partial shade resulting an additional 5 employment.